Gelatin extracted from rahu (Labeo rohita) and silver carp (Hypophthalmichthysmolitrix) scales and their beads efficacy as a carrier of inoculum and secondary metabolites - Roheela Yasmeen; Aisha Waheed Qurashi; Samreen Arif; Hina Qaiser (BioScientific Review, 2022)
Nowadays biological waste is increasing due to over population. At the same time, researchers are trying to use biological wastes in effective ways and trying to convert these wastes into useful products. In this study the scales of rohu (Labeo rohita) and silver carp (Hypophthalmichthys molitrix) were used for the extraction of gelatin. Chemical extraction method was mediated in the presence and absence of microbes to obtain gelatin from varying amounts of scales. Microbial isolates SCC5 from Silver carp and SEY from Labeo rohita were used for microbial extraction. Beads were prepared from extracted gelatin using three different types of oils and later used as a carrier of inoculum. Results showed that both isolates were positive for gelatin liquefaction liquifection and did not result in solidification even at low temperature when kept in the refrigerator. The amount of extracted gelatin from fish scales was less than 50 %. A pronounced increase was recorded when more than 30 gram of fish scales were used for extraction. It was noticed that beads prepared with natural gelatin were remained stable after washing and not degraded as compared to commercial gelatin. FTIR analysis of extracted gelatin showed the presence of peaks at 700, 1600 and 3400 nm range that were in line with peak trends of commercial gelatin. Beads were coated with antibiotic by soaking in the antibiotic dilution. From the zones formation of beads supplemented with the antibiotics it was observed that zone diameter increased as amount of antibiotic increased it means the beads have the capacity to carry the antibiotics. Moreover, t and beads of extracted gelatin were injected with the different inoculum  of bacterial isolatesgelatin beads can also be used as carrier of fertilizers in agriculture, which is a recent advancement in the field of agriculture.